PERAN SEKOLAH DAN PENDIDIKAN KESENIAN SEBAGAI PENGEMBANG ILMU PENGETAHUAN, TEKNOLOGI, MORAL, DAN AGAMA - Sugeng Bayu Wahyono (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Schools, as a formal education institution, are activities that are conscious, regular and planned to achieve certain goals. The role of school in building cultural awareness is highly expected. One way to achieve this is by developing continues and consistent art curriculum. Art is the expression of cultural processes. There are two types of cultural expression: progressive cultural expressions that are potential to advance science and technology and reflective cultural expressions that are potential to develop moral and religion value.